Polyhedral oligomeric silsesquioxane functionalized carbon nanotubes for high thermal conductive poly(vinylidene fluoride) composite membrane. (15th October 2018) - Song, Shasha; Cao, Min; Shan, Huiting; Du, Chunyu; Li, Baoan
Abstract: To achieve high thermal conductivity of polymer-based composites at low filler loading is still a challenge because of the insufficient contact area and incomplete thermal percolation pathway. In this work, PVDF composite membrane with high thermal conductivity is fabricated using polyhedral oligomeric silsesquioxane (POSS) functionalized carbon nanotubes (CNTs) as fillers. Surface modification promotes the uniform dispersion of CNT-POSS in PVDF matrix and enlarges the contact area. Through the thermal analysis of the CNT-COOH/PVDF and CNT-POSS/PVDF composites, the results indicate that the nucleation effect of CNTs increases the crystallinity of the pure PVDF from 42.9% to 51.2%. In addition, the addition of POSS nanoparticles to the CNT-PVDF composites significantly improves its thermal stability, mechanical and thermal conductivity properties. The CNT-POSS/PVDF composite membrane with 15 wt% CNT-POSS presents an extremely high thermal conductivity of 1.12 W/m·K (vs. 0.15 W/m·K for pure PVDF) and exhibits great superiority in comparison with the thermally conductive PVDF-based composites reported before. Graphical abstract: Highlights: POSS functionalized CNTs was applied to improve the dispersion state of fillers and PVDF matrix. The nucleation effect of CNTs increased the crystallinity of the pure PVDF from 42.9% to 51.2%. The mechanical, thermal stability and conductivity were further enhanced by the incorporation of POSS nanoparticles. Compared with the pure PVDF, the thermal conductivity of 15 wt % CNT-POSS/PVDF composite was increased 7.4 times.